CHARACTERISTICS OF TECHNOLOGIES OF GROWING PROSPECTIVE VARIETIES OF NON-TRADITIONAL VEGETABLE ARTICHOKE CROP - Alisher Juraboyevich Shakirov (Web of Journals Publishing, 2023)
The article talks about the characteristics of technologies for the cultivation of promising varieties of the non-traditional vegetable artichoke crop.
Keywords: vegetable, artichoke, crop, perspective, variety, cultivation, technology, feature.